The Effect of Financial Literacy and Financial Inclusion on Income Inequality in Indonesia - Aidillia Zulkarnain; Alpon Satrianto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
Income inequality is an economic phenomenon that has an impact on economic instability and the welfare of society. Indonesia's income inequality has not significantly improved or changed much from previous years. This study aims to analyze the effect of financial literacy and financial inclusion on income inequality in Indonesia. The type of research used in this study is quantitative research. The data used is panel data of 34 provinces in Indonesia in 2016, 2019, and 2022. The analysis method used is Panel Data Regression using the Random Effect Model (REM) approach. The results show that (1) financial literacy does not affect income inequality in Indonesia; (2) financial inclusion does not affect income inequality in Indonesia; (3) poverty has a significant positive effect on income inequality in Indonesia; and (4) wages has a significant negative effect on income inequality in Indonesia. Suggestions in this study: Financial institutions should start expanding the target of introducing new and existing products to increase public understanding and confidence, especially among the lower middle class. In addition, government intervention must be carried out massively and aggressively so that a general understanding of finance increases.